Pelatihan Penggunaan AI For Literature Review Untuk Guru di SDN 2 Merauke - Hanip, Rival; Irawan, Ferry (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
PkM methods conducted community education methods. This method aims to improve the understanding and skills of primary education teachers on how to review journal articles using AI. This coaching goes through six steps, namely: coaching conducts coaching, coaching contains aspects of knowledge, skills, and attitudes, coaching is expected to demonstrate behavior change as well as real action and influence the quality improvement of primary education pipeline teachers. The stages carried out are shown in Chart 1. The results of the activities show that the use of AI is very important in improving the learning process and able to train teachers to be accustomed to using the technology needed in facilitating the learning process, so that the participants and learners in the classroom are very interested in the process of using teachers. conditioning learning by using renewable Technology.